(untitled) (Research, Society and Development, 2022)
The Intensive Care Unit (ICU) is a place conducive to the treatment of critically ill patients, the adherence of pregnant women in the ICU most of the time is due to adequate adaptation in relation to prenatal care. Nursing care is of great importance, since the nurse is among all the professionals who provide this care to patients. Therefore, the objective of the present study was to describe the main nursing care and assistance to pregnant women in the ICU. This is an integrative literature review, based on the PICO method, where the literature search was carried out, in the Virtual Health Library (VHL) database, which is a tertiary source database, containing other databases such as MEDLINE , LILACS, IBECS etc. The following search strategy was used: “Pregnancy” AND “ICU” AND “Intensive Care Unit” AND “Nursing Care”. Initially, 258 studies were found in the VHL, with articles from MEDLINE, LILACS and IBECS. In the title selection process, 27 studies were selected, where, later, when reading abstracts, only 10 were selected for full reading. After applying the analysis and careful evaluation of the manuscripts, 04 studies were excluded because they did not adapt to the eligibility criteria, so there were 06 articles for the final. It is observed that nursing care in the ICU is care for the pregnant woman, mostly related to the monitoring of vital and hemodynamic signs. In addition, medical assistance was noted in the ICU.